Analysis Of Event Quality Effect On Satisfaction And Behavioural Intentions Of The Ramayana Ballet Attendees (Case Study Of Puspo Budoyo Culture House) - Roozana Maria Ritonga (Politeknik Sahid, 2019)
Event is becoming more increasingly important both socially and economically. Such growth has raised many questions concerning the quality of event and impact on satisfaction and behavioural intentions of attendees. With so many competitions in the event business, an event planner must increase the level of event quality. In order to create satisfaction and produce revisit of attendees in the event, a high quality of performance, employees and environment is highly recommended. This study examines the underlying structure of event quality and impact between satisfaction and behavioural intentions. Three event quality dimensions (quality of event employees, quality of event environment, and event product quality) are examined with descriptive statistical method and regression analysis. This study is based on the cultural event of ‘Ramayana Ballet’ performance at Culture House of Puspo Budoyo. The results of this research shows that event quality has a significant relationship between satisfaction and behavioural intentions. On the other hand, quality event employees, quality event environment and quality event product have significant impact on behavioural intentions.